Pharmacotherapy for the treatment of vaginal atrophy. (3rd May 2019) - Donders, Gilbert G. G.; Ruban, Kateryna; Bellen, Gert; Grinceviciene, Svitrigaile
ABSTRACT: Introduction : Despite its frequency, recognition and therapy of vulvovaginal atrophy (VVA) remain suboptimal. Wet mount microscopy, or vaginal pH as a proxy, allows VVA diagnosis in menopause, but also in young contraception users, after breast cancer, or postpartum. Intravaginal low dose estrogen product is the main therapy. Ultra-low-dose vaginal estriol is safe and sufficient in most cases, even in breast cancer patients, while hyaluronic acid can help women who cannot or do not want to use hormones. Areas covered : The authors provide an overview of the current pharmaceutical treatment for vulvovaginal atrophy and provide their expert opinions on its future treatment. Expert opinion : The basis of good treatment is a correct and complete diagnosis, using a microscope to study the maturity index of the vaginal fluid. Minimal dose of estriol intravaginally with or without lactobacilli is elegant, cheap and can safely be used after breast cancer and history of thromboembolic disease. Laser therapy requires validation and safety data, as is can potentially cause vaginal fibrosis and stenosis, and safer and cheaper alternatives are available.